Beyond creativity! Exploring the nexus of entrepreneurial self-efficacy and intellectual agility-resonance on entrepreneurial intention among Generation Z - Alicia Stephanie Gunawan; Elia Ardyan (Universitas Muhammadiyah Yogyakarta, 2024)
This research investigated the significance of entrepreneurial self-efficacy and intellectual agility-resonance in influencing entrepreneurial intention among individuals from the Generation Z cohort. The research is grounded in Social Cognitive Theory (SCT). The research sample consisted of 279 students who were engaged in entrepreneurial activities on campus. This study uses structural equation modeling partial least squares (SEM-PLS). The findings demonstrated that entrepreneurial creativity had the potential to enhance both entrepreneurial self-efficacy and intellectual agility-resonance. Moreover, the combination of entrepreneurial self-efficacy and intellectual agility-resonance could enhance the entrepreneurial intention of individuals belonging to Generation Z. Other studies have demonstrated that entrepreneurial inventiveness does not have a direct impact on entrepreneurial ambition. An essential factor in connecting the impact of entrepreneurial creativity to entrepreneurial intention includes entrepreneurial self-efficacy and intellectual agility-resonance as mediators. The results expanded Social Cognitive Theory by giving empirical evidence concerning the significant role of entrepreneurial self-efficacy and intellectual agility-resonance in mediating the link between entrepreneurial creativity and entrepreneurial intention. These findings corroborated SCT's perspective that personal and cognitive elements were crucial in developing entrepreneurial behavior and gave practical implications for boosting entrepreneurship education and development among Gen Z.